Galaxies in the Local Volume - Koribalski, Bärbel Silvia; Jerjen, H.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2008)
Studies of Nearby Galaxies are currently the focus of many observations and numerical simulations. This book presents an overview of the galaxies within the Local Volume (D < 10 Mpc), including the Local Group (D < 1 Mpc) and our closest neighbours, the Andromeda Galaxy and the Magellanic Clouds. Presented are the latest results from radio, infrared and optical surveys as well as detailed multi-wavelength studies of individual galaxies. Accurate distances are now available for the majority of Local Volume galaxies providing a true 3-dimensional view of their distribution and flow pattern as well as their star formation.
Keywords: Astrophysics; Space sciences; Observations, Astronomical; Astronomy—Observations.; Astronomy; Astrophysics and Astroparticles; Space Sciences (including Extraterrestrial Physics, Space Exploration and Astronautics).; Astronomy, Observations and Techniques; Astronomy, Astrophysics and Cosmology